Evolution of public broadcasting: TeleJurnal’s viewership trends and strategic implications for business sustainability - Săseanu Ramona; Stanomir Ruxandra; Bădulescu Andreea-Alexandra (Management şi Marketing)
As traditional public broadcasting contends with a more competitive digital environment, Romania’s national broadcaster, Televiziunea Română, confronts crucial questions regarding audience engagement from a business standpoint. This research examines the viewership trends of TeleJurnal, the network’s main flagship news program, utilizing data from 2018 to 2022, and projects forecasts for 2023–2025. By employing a time-series autoregressive moving-average model, this article assesses the stationarity and autocorrelation of audience data to evaluate the consistency of ratings amidst external factors such as changes in programming strategy, political events, and market competition. The results show notable steadiness in TeleJurnal’s viewership, offering considerable strategic benefits and allowing for more assured long-term planning for programming and revenue generation. The consistent audience patterns we identified enhanced the broadcaster’s position in advertising discussions and supported more precise budget forecasts while revealing opportunities to capitalize on seasonal viewing trends for optimized advertising revenue. Nonetheless, financial limitations and digital disruption may alter audience tastes and diminish the effectiveness of conventional television formats. By implementing data-centric content creation and business planning strategies, TeleJurnal can sustain its competitiveness and fulfill its duty as a public service entity in a changing media environment. The insights derived from this study provide actionable advice to maintain audience fidelity, enhance financial outcomes, and adjust to evolving market dynamics.